The Influence of Profitability, Liquidity, and Company Size on Sustainability Report Disclosure with the Audit Committee as a Moderating Variable - Rahayu, Sukma Purnama; Handayani, Bestari Dwi (Ilomata International Journal of Management, 2026)
This study aims to examine the influence of profitability, liquidity, and company size on the level of sustainability report disclosure in companies included in the LQ45 Index during the 2022–2024 period, with the audit committee as a moderating variable. This study was conducted to fill the gap in previous research that was still limited to testing the existence of an audit committee alone or using the period before the strengthening of sustainability reporting regulations after 2021, and had not examined in depth the quality of the audit committee's role in moderating company characteristics. The study used a quantitative approach with a purposive sampling technique, and was analyzed through Moderated Regression Analysis (MRA) based on secondary data obtained from the Indonesia Stock Exchange and the company's official website. The results of the analysis showed that profitability and liquidity did not have a significant effect on sustainability report disclosure, while company size had a positive and significant effect. The audit committee was shown to significantly moderate the relationship between profitability and sustainability disclosure, but with a negative coefficient direction, indicating that the oversight role can limit the tendency for over-disclosure. Conversely, the audit committee did not significantly moderate the relationship between liquidity and sustainability report disclosure. In the relationship between company size and sustainability disclosure, the audit committee also acts as a significant moderator with a negative coefficient, indicating that the audit committee's oversight role can limit the tendency of large companies to make excessive, symbolic disclosures.